Proof of concept of a novel frictional shock absorber; analytical model and experimental analysis. (1st March 2021) - Maureira-Carsalade, N.; Villagrán-Valenzuela, M.; Sanzana-Jara, D.; Roco-Videla, A.
Graphical abstract: Highlights: Development of a mathematical model that predicts the behavior of a novel self-centering impact shock absorber with dissipation capacity by friction. The device's analytical model has been extensively validated using experimental results obtained from a large number of tests with variable impact energy. Numerical simulations and experimental results verify the excellent device performance, specially their high dissipative capacity and the reduction of the rebound speed after the impact. There are many practical applications for this novel device that can be explored using the analytical model presented on this paper. Abstract: Recurrent impact protection devices usually need to dissipate large amounts of energy to prevent damage to the infrastructure they protect and to make efficient use of them. This requires that protection devices consider some type of damping and have some mechanism to recover their original form. In this study a novel device is proposed, capable of absorbing a large part of the energy imposed by impact loads and recovering its original form autonomously. The device proposed in this article is composed of rigid parts with articulated joints, an elastic element that allows the recovery of its shape and an element that dissipates energy by friction. The necessary equations were developed to describe the non-linear behavior of the device and parametric simulations of the proposed model were performed to describe the dynamic interaction between the device and a mass that impacts. Additionally, a scale model of the device was constructed to be experimentally tested, which allowed to verify the effectiveness in the dissipation of energy, the reduction in the force transmitted to the support structures and the decrease in the rebound speed of the impacting mass. An error parameter was defined for a load-unload cycle between experimental results and analytical calculations. The error considers both the impact force and the dissipated energy, obtaining values of up to 6%. The energy absorption capacity of the device –between 83% and 93% of the impact energy– was verified experimentally, as well as the reduction of the impact speed –between 91% and 96%–.